Larvicidal Activity of Citrus Limonoids against Aedes albopictus Larvae - Hazrat Bilal; Waseem Akram; Soaib Ali-Hassan (Tehran University of Medical Sciences, 2012)
Background: Development of insecticide resistance occurred due to the continuous and misuse of synthetic insecticidestherefore, the recent study was conducted to explore eco-friendly plant extracts that have some potential to suppressmosquito larval population.Methods: WHO recommended mosquito larval bioassay method for insecticide was used while for the analysis of citrus oils for limonin and nomilin content HPLC was used.Results: Among the two citrus cultivars tested as larvicide against Aedes albopictus, valencia late (Citrus sinensis) wasthe best in terms of LC50 (297 ppm), % mortality (97%) and LT50 (18.49 hours) then freutrall early (Citrus reticulate)with LC50 (377.4 ppm), % mortality (88%) and LT50 (31 hours), While nomilin gave lowest LC50 (121.04 ppm) than limonin (382.22 ppm) after 72 hours of exposure. Valencia late also had more limonin and nomilin (377 μg/ml and 21.19 μg/ml) than freutrall early (5.29 μg/ml and 3.89 μg/ml) respectively.Conclusion: Valencia late showed best results in term of LC50, LT50 and percentage mortality against Aedes albopictus as it has more amount of nomilin then freutrall early, however further evaluation in the field conditions is required.